ANALISIS METAKOGNITIF SISWA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH PADA MATERI LUAS GABUNGAN BANGUN DATAR - Firda Rizky Amelia; Jatmiko; Aprilia Dwi Handayani (Afore : Jurnal Pendidikan Matematika, 2026)
This study aims to describe students’ metacognitive skills in solving mathematical problem-solving tasks on composite plane figures. A qualitative descriptive approach was employed. The subjects were three fifth-grade students of SDN Blabak 1 Kota Kediri, selected through purposive sampling and categorized into high, medium, and low mathematical ability levels. Data were collected through written tests, semi-structured interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing. The instruments were developed based on the metacognitive indicators of Jacobse and Harskamp: orientation, planning, evaluation, and reflection. The results show that students with high mathematical ability demonstrate well-developed metacognitive skills across all indicators, students with medium ability exhibit partial metacognitive regulation, and students with low ability show weak metacognitive control. These findings emphasize the importance of strengthening metacognitive strategies in mathematics learning.